Phenotypic characterization, plant growth and development, genome methylation, and mineral elements composition of neotetraploid lettuce (Lactuca sativa L.) - Simko, Ivan; Zhao, Rebecca (Frontiers in Plant Science, 2023)
Stable neotetraploid lines of lettuce (Lactuca sativa L.) were produced from three phenotypically distinct cultivars (Annapolis, Eruption, Merlot) and an advanced breeding line (SM13-L2) using colchicine treatment of seeds or young seedlings. When tested under the greenhouse and field conditions, neotetraploids initially grew more rapidly than their diploid progenitors, however they reached their reproductive stage (bolting, flower bud formation, and flowering) substantially later. Seeds production on neotetraploids was delayed by more than 30 days compared to diploids. Tetraploid plants had fewer, but larger stomata and leaves, less chlorophyll per area, higher photosystem II photochemical efficiency, generally lighter root system, and produced less than 1% of seeds in comparison with diploids. Field-grown neotetraploids of all lines displayed a significant reduction in tipburn (1.8% vs. 22.2%, respectively), a highly undesirable physiological disorder. Changes in leaf and root mineral composition were detected in neotetraploids. Several elements were found in lower abundance than in diploids, most notably iron, calcium, and silicon. Whole genome bisulfite sequencing (WGBS) revealed 498 differentially methylated regions (DMR), with 106 of these regions having at least 50% difference in the level of methylation between neotetraploids and their diploid progenitors. At least 18 of the most prominent DMR were detected in proximity to genes predicted to be involved in plant development or reaction to biotic and abiotic stressors. Because neotetraploid lines have low seed production, they are not suitable for commercial cultivation. They can be used, however, in research to study the factors contributing to tipburn, traits affected by stomata size or density, and the effect of ploidy on resistance to environmental stressors.